'The Worst Oratorio Ever!': Colonialist Condescension in the Critical Reception of George Tolhurst's Ruth (1864). Issue 2 (4th May 2017) - Kirby, Sarah
Abstract : The oratorio genre was regarded amongst the most edifying and instructive artforms of the Victorian era, and it was to these lofty ideals that George Tolhurst (1827–1877) aspired when composing his 1864 oratorio Ruth . The first work of its kind written in the British colony of Victoria, Australia, Ruth received an initially favourable local reception; Tolhurst was urged by the Melbourne press to aim higher and present his work to a wider and more discerning audience. Consequently, he took his work to London where it was roundly criticized, widely mocked and eventually dubbed 'the worst oratorio ever'. It might be assumed that a work so poorly received in the cultural metropolis of London would be, like so much other Victorian music, immediately forgotten. However, through its notoriously bad reception, Ruth – in what Percy Scholes describes as a 'succès de ridicule' – found a cult following that has spanned from the nineteenth century to the present day. This article examines the critical reception of Ruth through the lens of colonial social relations, arguing that the treatment of Ruth in both London and Melbourne is emblematic of broader trends in the nineteenth-century relationship between parent state and settler colony. It also explores the surprising phenomenon of twentieth- and twenty-first-century consumption of Ruth in Britain, questioning whether the legacies of certain Victorian social and cultural prejudices relating to the artistic products of the colonies have been mitigated. Aesthetic and representational decisions made in recent revivals of Ruth suggest that cultural hierarchies forged during the Victorian era continue to be reinforced in the present day.